Fortunella spp., Kumquat - Michael G. Andreu; Melissa H. Friedman; Robert J. Northrop (EDIS)
Many people find kumquat trees attractive and useful yard specimens. Their dark green leaves and contrasting bright orange fruits give them ornamental quality, and their relatively small size makes them easy to care for once they’re established. Because kumquats generally require less care than other citrus trees, they may be a good choice for gardeners with less time or experience, but who still desire an attractive and tasty citrus tree. If space is an issue, kumquats also do well in containers as long as they receive proper sunlight and watering. This 2-page fact sheet was written by Michael G. Andreu, Melissa H. Friedman, and Robert J. Northrop, and published by the UF Department of School of Forest Resources and Conservation, July 2012.